New Practices оf Engineering Education in Conditions of Distance Learning - T. A. Olkhovaya; E. V. Poyarkova (Высшее образование в России, 2020)
The paper focuses on the analysis of the experience of the university’s rapid transition to the distance learning format, with the emphasis on the introduction of tools for the development of educational interaction between tutors and students in order to prepare engineering students with competencies in information and cross-cutting technologies. The experience of introducing digital services to support the educational process at Orenburg State University is analyzed; an analysis is made of the students’ comprehensive perception of the new educational practice specifics associated with the creation of the “digital footprint”. The presented data show an increase in students’ demand for flexible individual educational paths, for a variety of forms of learning and for the formation of new competencies in the field of digital skills, creativity, the ability to self-learn and manage attention, create communities, and reflectivity. The authors argue that the digital competence of engineering graduates must exceed the existing range of competencies in order to work ahead of the situation. Attention is paid to the development in the distance learning format of basic personal skills that contribute to the formation of professional capital of a future engineer.